The role of chemotherapy in the management of olfactory neuroblastoma: A 40‐year surveillance, epidemiology, and end results registry study. Issue 2 (2nd May 2021) - Brisson, Ryan J.; Quinn, Thomas J.; Deraniyagala, Rohan L.
Abstract: Background: In this retrospective surveillance, epidemiology, and end results (SEER) registry analysis, we investigated the role of chemotherapy (CT) in the treatment of olfactory neuroblastoma (ON), an exceedingly rare sino‐nasal tumor typically treated with surgery and/or radiation therapy (RT). Methods: We analyzed all patients in the SEER registry diagnosed with a single primary malignancy of ON, a primary tumor site within the nasal cavity or surrounding sinuses, sufficient staging information to derive Kadish staging, and >0 days of survival, ensuring follow‐up data. Receipt of CT in the SEER registry was documented as either Yes or No/Unknown. Results: Six hundred and thirty‐six patients were identified. One hundred and ninety‐five patients received CT as part of their treatment for ON. Following propensity score matching and inverse probability of treatment weighting, there was inferior overall survival (OS) (HR 1.7, 95% CI: 1.3‐2.2, P = .001) and cancer‐specific survival (CSS) (HR 1.8, 95% CI: 1.3‐2.4, P  < .001) for patients who received CT compared to those who were not treated with CT or had unknown CT status. On subgroup analysis, the only patient population that derived benefit from CT were patients who did not receive surgery and were treated with CT and/or RT (HR 0.3, 95% CI: 0.14‐0.61, P  < .001). Conclusions: Based on this retrospective SEER registry analysis, the use of CT in the management of ON is associated with decreased OS. Our analysis suggests that patients who are considered nonsurgical candidates may benefit from the addition of CT.